PELATIHAN PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN BANK SAMPAH BERBASIS EKONOMI SIRKULAR DI DESA SUKORENO, PRIGEN, PASURUAN - Muliatie, Yurilla Endah; Sarie, Rena Febrita; Antopani, Tendi; Putra, Deny Namanda; Handayani, Rofiqo Dian Agustin; Herdiansyah, Raditya; Paramita, Lungayu Indraswari; Prayoga, Handi Lambang; Alfiah, Siti; Danggur, Kristoforus; Islam, Muhammad Syahfiqul (STIE Pelita Nusantara, 2025)
Solid waste management has become a pressing environmental issue in Indonesia, with more than 68 million tons of waste generated annually, of which a large portion remains unmanaged. Sukoreno Village, located in Prigen District, Pasuruan Regency, faces significant challenges in handling 2–2.5 tons of daily household waste that is not separated at the source, resulting in environmental degradation and health risks. This community service program aimed to empower local communities through training on waste management based on the circular economy concept, particularly by establishing and operating a community-based waste bank. The program was carried out through socialization, technical training, technology implementation, and continuous mentoring. Results showed a substantial improvement in community awareness, with 70% of households understanding the importance of waste segregation and 50% beginning to implement it. Technical training enabled residents to acquire practical skills in waste bank management, composting, plastic recycling, and maggot cultivation, leading to the formation of three new community business groups. Furthermore, the installation of a waste sorting machine and a plastic shredder, along with the construction of a 3R Waste Processing Site (TPS 3R) and a village waste bank, significantly enhanced processing capacity to 100 kg of waste per day and 500 kg per month, respectively. The program also reduced waste disposal to landfill by 40% and increased village income by 15% within the first three months, with a projected growth of 20% annually. These outcomes highlight that circular economy-based approaches not only reduce environmental burdens but also create economic opportunities, strengthen social cohesion, and support the achievement of Sustainable Development Goals (SDGs), particularly Goal 11 on sustainable cities and communities and Goal 12 on responsible consumption and production.